Nutrition and development : short and long term consequences for health - Wyness, Laura; Stanner, Sara.; Buttriss, Judith; British Nutrition Foundation (Chichester, West Sussex : published by Wiley-Blackwell for the British Nutrition Foundation, 2013)
This latest report from the British Nutrition Foundation comprehensively covers the subject of Developmental Programming and Diet. This book covers programming factors involved in the vulnerabilities in early development to nutrients and looks in detail at the relationship between nutrition during critical phases of development and disease risk later in life and includes coverage of obesity, diabetes, cardiovascular disease, cancer, bone health and psychiatric health. All nutritionists, dietitians and those working in developmental programming, including physiologists, endocrinologists, epidemiologists and developmental biologists will find a huge wealth of important and thorough information within this new Task Force Report.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Nutritional Physiological Phenomena; Human development; Nutrigenomics -- methods; Nutrition; Nutrition -- Development; HEALTH & FITNESS -- Diets; HEALTH & FITNESS -- Food Content Guides; HEALTH & FITNESS -- Nutrition; MEDICAL -- Nursing -- Nutrition; MEDICAL -- Nutrition; Electronic books; Electronic books